Instruction of jump-landing technique using videotape feedback - Altering lower extremity motion patterns - Onate, J. A.; Guskiewiscz, K. M.; Marshall, S. W.; Giuliani, C.; Yu, B.; Garrett, W. E. (The American Journal of Sports Medicine, 2005)
Background: Anterior cruciate ligament injury prevention programs have used videotapes of jump-landing technique as a key instructional component to improve landing performance.